Participation in and use of skills development for work ability and expected retirement age: a cross-sectional study among senior workers - Seeberg, Karina Glies Vincents; Skovlund, Sebastian Venge; Sundstrup, Emil; Mortensen, Ole Steen; Andersen, Lars Louis (Frontiers in Public Health, 2025)
IntroductionEurope’s aging population calls for ways to prolong working life. Skills development initiatives could potentially improve work ability and extend working lives and may thus be key to address this challenge. However, the role of skills development in relation to work ability and retirement age is still not fully understood.AimThis study aims to investigate the association of skills development with work ability and expected retirement age among senior workers.MethodsIn 2022, all State employees in Denmark aged 55 years or above (n = 53,673) received a web-based questionnaire, of which 42% were included in the analyses (n = 22,544). The questionnaire included questions about participation in skills development initiatives over the past 2 years, lifestyle and work environment, including work ability and expected retirement age. We employed Generalized Linear Models (GLMs), weighted for Union, sex and age, with multivariate adjustment to examine associations of participation in (1) courses, (2) formal education, and (3) other forms of skills development on work ability and expected retirement age.ResultsFormal education showed associations with expected retirement age with a between-group difference of 0.68 years Confidence Interval (CI) (0.54 to 0.82). Conversely, other forms of skills development (peer-to-peer training or self-study) were most positively associated with work ability in specific models with a between-group difference of 0.20 years CI (0.16 to 0.24).ConclusionOur findings suggest that participation in skills development is positively associated with work ability and expected retirement age. These findings underscore the need for targeted skills development programs, which may enhance workforce sustainability and help workers prolong their working life.